Clinical performance of the composite resin veneers: the minimally invasive approach - Bastos, Natália Almeida; Scotti, Cassiana Koch; Zabeu, Giovanna Speranza; Bueno, Ligia Saraiva; Ferrairo, Brunna Mota; Bombonatti, Juliana Fraga Soares (ARCHIVES OF HEALTH INVESTIGATION, 2018)
Minimally invasive approach lead composite resin veneers restorations as a conservative and alternative treatment option, with the aim to improve the aesthetics anterior dentition. Clinically, this treatment reducing the clinical time and has a lower cost than indirect technique. In addition, new resin composite was developed to support the clinician to make more natural restorations. The present case report aim to evaluated the clinical performance of direct composite veneer technique was restored with 100% supra-nano spherical filler composite. A 39-year-old female, searched for restorative treatment of anterior teeth, which were unaesthetically altered. In the clinical examination, it was observed color alterations in maxillary left and right incisors and canines due to use of medicines, and bruxism. The treatment plan included an in-office dental bleaching, removal of inadequate anterior restorations and confection of composite veneers restorations. The dental bleaching was performed with hydrogen peroxide 35% activated by LED/laser in two sessions. Those restorations were performed using supra-nano spherical resin-based composite, color A1 for dentin and enamel, with direct composite laminate veneer technique. After six-month follow-up, the restorations presented good clinical aspect, absence of biofilm accumulation and abrasive wear. Therefore, direct veneer restorations may be alternative treatment for anterior teeth esthetic problems, suggesting a promising performance of these new composites. Descriptors: Esthetics, Dental; Composite Resins; Dental Veneers.